Limbic system associated membrane protein as a potential target for neuropsychiatric disorders - Vasar, Eero; Innos, Jürgen; Philips, Mari-Anne; Koido, Kati (Frontiers in Pharmacology, 2013)
The studies performed in laboratory animals and psychiatric patients suggest a possible role of limbic system associated membrane protein (LAMP) in the mechanisms of psychiatric disorders. Stressful manipulations and genetic invalidation have revealed a role of the Lsamp gene in the regulation of anxiety in rodents. Besides that, Lsamp deficient mice display reduced aggressiveness and impaired adaptation in novel and stressful environments. The behavioural effects of amphetamine were blunted in genetically modified mice. Recent pharmacological and biochemical studies point towards altered function of GABA-, 5-hydroxytryptamine- and dopaminergic systems in Lsamp deficient mice. Moreover, we found an association between the gene polymorphisms of LSAMP and major depressive disorder. Patients suffering from major depressive disorder had significantly increased ratio between risk and protective haplotypes of the LSAMP gene compared to healthy volunteers. However, the impact of these haplotypes for the function of LAMP is not clear and remains to be elucidated in future studies.